DETEKSI TEPI MENGGUNAKAN METODE KIRSCH UNTUK MEMBEDAKAN KERUDUNG SYAR’I DAN KERUDUNG MODERN (Information Technology and Telematics, 2014)
Abstract In the era of globalization makes the model veil that has now become a fashion , so that women seem more confident in wearing the veil , and that is what is referred to as a modern veil . While the veil that veils Sharai good having such terms cover the entire body except the exempted , not to ornate , not revealing curves , and do not invite the attention of men . With this application can help in detecting the edge of the hood to obtain the type of veil worn . Subject of this research is to create a system implementation Kirsch edge detection methods into the detection of the type of veil . The data used is a sample image of women wear the veil Syar’i as many as 20 images , 20 images of modern hoods , and without hoods with extensions and 10 images of different brightness levels . By using image processing , the image will be tested undergo repair process that aims to improve the image quality and contrast of an image Kirsch edge detection method is used to find the initial information . The results showed that the type of hood edge detecting method can detect the type of veil Kirsch with 70 % accuracy , with the image type and the type of extension does not affect the accuracy of the image edge detection . As for affecting the level of test images kekuratan ie background , pattern dress , veil indentation , facial expressions , and the grouping boundaries overlap.Keyword : Edge detection, The veil, Kirsch method